Study of phytopathogenic fungi of Ipomoea hederifolia L.: an invasive weed in agricultural crops in Brazil - Mira, Yerly [UNESP]; Pieroni, Lisandro [UNESP]; Benso, Lucas [UNESP]; Álvarez, Yasir; Rossini, Bruno [UNESP]; Furtado, Edson [UNESP]; Velini, Edivaldo [UNESP] (Springer Nature, 2024)
Ipomoea hederifolia L. is a weed that is considered problematic in several tropical crops. Phytopathogenic mycobiota could provide an alternative approach to biological weed management in agriculture. The objective of this study was to isolate and identify phytopathogenic fungi against I. hederifolia, under the inundative approach to biological control. The isolated fungi were subjected to pathogenicity tests in the laboratory through bioassays on detached leaves. The response variables recorded were incubation period, disease incidence, and the area under the disease progress curve (AUDPC). The fungi of interest were characterized morphologically and identified by molecular studies. The most aggressive pathogen was evaluated in a greenhouse by bioassays on whole I. hederifolia seedlings, using two inoculation methods: (1) agar disks with mycelium and (2) conidial suspension. Three of the eight fungi obtained were found to have pathogenic potential against the weed and were identified as Alternaria longipes, Cochliobolus geniculatus and Phoma herbarum. In the detached leaf bioassays, the incidence of the disease was greater than 81% in all cases and the average incubation period was between 3.4 and 4.5 days. A. longipes was significantly the most aggressive isolate (AUDPC = 9.1). In the bioassays on whole seedlings, 83% and 33% of the seedlings were infected by A. longipes using methods (1) and (2), respectively, after 10 days. We conclude that our isolate of A. longipes could be useful as a possible biocontrol agent for this weed; however, it is important to continue the next research steps of the inundative approach to confirm its suitability.
Keywords: Alternaria; Biological control; Morning glory; Phytopathogenic fungi; Weed management